Villagers protect Ghanaian wetlands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In order to protect the mangrove forest in the Sakumono Lagoon the Ghanaian Wildlife Society, an NGO, has developed concerted plans and activities with local communities. In exchange for improvements in their village s infrastructure and support...